INTERFERENCE IN LEAFLETS FROM ENGLISH INTO ACEHNESE LANGUAGE - Riska Nazirah; Rahmatun Nisa; Elfia Elfia (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2019)
The aims of this study are to identify the phrases from English into Acehnese that found by the writer in leaflets, to know the factors of the shop owners interfered the phrases, and to find out the interpretation of each visitor toward those phrases. In collecting of the data, the writersobservedthe leaflets and interviewed the owners of coffee shops and some visitors who visited these coffee shops in Banda Aceh. The result of the analysis on interference in leaflets from English into Acehnese, the writers found 6 phrases; 4 phrases got from coffee shops and 1 from a sticker. And, after interviewing some owners and more than 25 visitors who visited the coffee shops. they got ownersâ€™reasonswhy created the phrases because they have own histories and wanted different from others coffee shops. In interpreting the phrasessome of visitorsunderstood Â the aim of owners created the phrases while the others did not, Then, the reason of visitors visited these coffee shops was not about a name or logo but about the service of the waiter and the convenience of the place.